2019
DOI: 10.1002/chem.201904114
|View full text |Cite
|
Sign up to set email alerts
|

π‐Conjugated Macrocycles Bearing Angle‐Strained Alkynes

Abstract: Angle‐strained alkyne‐containing π‐conjugated macrocycles are attractive compounds both in functional materials chemistry and biochemistry. Their interesting reactivity as well as photophysical and supramolecular properties have been revealed in the past three decades. This review highlights the recent advances in angle‐strained alkyne‐containing π‐conjugated macrocycles, especially their synthetic methods, the bond angles of alkynes (∠sp at C≡C−C), and their functions. The theoretical and experimental researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 419 publications
(909 reference statements)
0
24
0
1
Order By: Relevance
“…Unfortunately, there is no computational benchmark or easily obtainable experimental data for strain and the amount determined can vary depending on the technique used. For example, [12]CPP has a range of strain energies depending on the computational technique (summarized in Table 1). Given this relatively wide range in the literature, there is signicant room for error in any new computational method.…”
Section: Energies Are Expectedly Similar To Previous Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is no computational benchmark or easily obtainable experimental data for strain and the amount determined can vary depending on the technique used. For example, [12]CPP has a range of strain energies depending on the computational technique (summarized in Table 1). Given this relatively wide range in the literature, there is signicant room for error in any new computational method.…”
Section: Energies Are Expectedly Similar To Previous Resultsmentioning
confidence: 99%
“…Macrocyclic strain is leveraged in chemical biology for bioorthogonal reactivity 1,2 and in polymer chemistry for ring opening metathesis. 3,4 Additionally, graphitic macrocycles, such as carbon nanohoops, 5 have enhanced solubility, 6 remarkable photophysical properties, 7,8 and reactivity [9][10][11][12] that all arise from strain. These attributes, and improvements in methods for their synthesis, [13][14][15][16] have caused a renewed interest in strained macrocyclic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Jasti and co-workers prepared a series of strainedalkyne cycloparaphenylenes (CPPs) 41 whose size and reactivity can be precisely tuned. 42,43 Similar to the pyrenophanes described above, it was experimentally found that the reactivity of the system having seven phenylenes in its structure (18a) is markedly higher than that of its larger counterparts (18c and 18e, Scheme 3). We then decided to apply our ASM-EDA approach to shed more light on the factors controlling the reactivity of these species, 44 which is crucial for the design of new strained "clickable" and radially oriented p-rich macrocycles.…”
Section: (A) Reactivity Of Pyrenophanesmentioning
confidence: 62%
“…We then decided to apply our ASM-EDA approach to shed more light on the factors controlling the reactivity of these species, 44 which is crucial for the design of new strained "clickable" and radially oriented p-rich macrocycles. 43 To this end, we considered the Diels-Alder cycloaddition reaction involving cyclopentadiene and the alkyne embedded CPPs 18a-e, having seven to eleven phenylenes in their structures. Similar to the reactivity of pyrenophanes, our calculations conrm that the reactivity of these CPPs steadily decreases with an increase of the size of the system up to the limit of the corresponding planar counterpart diphenylacetylene (DPA).…”
Section: (A) Reactivity Of Pyrenophanesmentioning
confidence: 99%
“…Well-defined π-conjugated macrocycles have attracted considerable attention from researchers because they not only are theoretically and experimentally interesting, but they also demonstrate potential applications in carbon-based nanoelectronics. [1][2][3][4][5][6][7][8] In particular, the cyclo-p-phenylenes have been well developed during the past decade, due to their unique structures, optoelectronic properties, and supramolecular host-guest behavior. [9][10][11][12][13][14][15] Anthracene is a versatile synthon that is widely used to synthesize attractive and functional molecules in organic electronics, due to its molecular panel-like shape and excellent photophysical properties.…”
Section: Introductionmentioning
confidence: 99%